Raavan : - Amish (Westland Publications, 2019)
A resolve to be a giant among men, to conquer, plunder, and seize the greatness that he thinks is his right. A man of contrasts, of brutal violence and scholarly knowledge. A man who will love without reward and kill without remorse.This exhilarating third book of the Ram Chandra series sheds light on Raavan, the King of Lanka. And the light shines on the darkness of the darkest kind. Is he the greatest villain in history or just a man in a dark place, all the time?